Mutation analysis of the EBV‐lymphoblastoid cell line cautions their use as antigen‐presenting cells. Issue 2 (18th December 2017) - Tan, Qin; Ku, Wenjing; Zhang, Chaoting; Heyilimu, Palashati; Tian, Yuan; Ke, Yang; Lu, Zheming
Abstract: Lymphoblastoid cell lines (LCLs) have been widely used as professional antigen‐presenting cells (APCs). However, neoantigen‐loaded LCLs could induce nonspecific T‐cell response, which could be due to expression of both Epstein–Barr virus (EBV) antigens and nonsynonymous mutations arising in LCLs. Since the number of passages could influence mutational characteristics of LCLs, and moreover extensive proliferation of LCLs in vitro is necessary to activate T cells for immunotherapy, we comprehensively profiled mutational characteristics by comparing eight sets of B cells and matched high‐passage LCLs using whole‐exome sequencing in order to assess the effect of nonsynonymous mutations arising in LCLs on nonspecific T‐cell response. We found 315 nongermline mutations (approximately 40mut/subject) randomly distributed across all chromosomes including 18 mutations in immunoglobulin V and J genes in eight LCLs, of which 137 candidate neoantigens (approximately 17mut/subject) were identified. The underlying mutational processes linked to EBV‐transformed LCLs could be attributed to activation induced cytidine deaminase gene expression which contributes to cytosine mutation clusters in LCLs through cytosine deamination. Pathways significantly enriched by nonsilent mutations of each LCL were totally different among all LCLs. In conclusion, high‐passage LCLs may not be suitable to serve as APCs due to random nonsilent mutations, particularly for presentation of neoantigens of low immunogenicity, although further experimental proofs are needed. Abstract : High‐passage lymphoblastoid cell lines may not be suitable to serve as antigen presenting cells due to random nonsilent mutations, particularly for presentation of neoantigens of low immunogenicity, although further experimental proofs are needed.